A Critical Discourse Analysis Of Religious Tolerance in ELT Textbook for Senior High School - Ikawati, Fifi Nur; Setyono, Budi; Rofiq, Annur (EFL Education Journal, 2023)
This study was conducted to investigate how religious tolerance portrayed in ELT textbook for senior high school students for grade 10. The present study applied critical discourse analysis (CDA), framed in fairclough’s 3D model approaches in analyzing visual and textual artifact materials that represents the religious tolerance in the textbook. The findings showed that religious tolerance has very rare found in the textbook, which is represented 6 times through different images and oral text. The visual and textual data of religious tolerance contained in each textbook unit have been identified using the categories of fairness (F), respect (R1), and reasonableness (R2). The findings showed that there is still a lack of visual and verbal representation of religious tolerance in the textbook.